The association between antenatal indomethacin exposure and persistent pulmonary hypertension of the newborn in extremely preterm infants - Chuncai Xu; Yingying Bao; Huanhuan Ding; Kaijian Wang; Qianyu Yang; Jiajun Zhu (Scientific Reports)
Abstract The study aimed to investigate the association between antenatal indomethacin exposure and persistent pulmonary hypertension of the newborn (PPHN) in extremely preterm infants. A retrospective cohort study was conducted involving extremely preterm infants admitted from January 2022 to May 2024. Neonates were categorized into the indomethacin group and the control group based on the antenatal indomethacin exposure. The primary outcome focused on the incidence of PPHN, while secondary outcomes encompassed the incidence of moderate to severe bronchopulmonary dysplasia (BPD), mortality, respiratory distress syndrome (RDS) ≥ stage III, hemodynamically significant patent ductus arteriosus (hsPDA), spontaneous intestinal perforation (SIP), intraventricular hemorrhage (IVH) ≥ grade III, surgical necrotizing enterocolitis (NEC) and retinopathy of prematurity (ROP) ≥ stage 3. Among the 203 included neonates, there were 68 neonates in the indomethacin group and 135 neonates in the control group. A significant association was observed between antenatal indomethacin exposure and the incidence of PPHN in extremely preterm infants (OR, 6.435; 95% CI, 1.263–32.795; P = 0.031). Among the secondary outcomes, the incidence of pneumothorax in indomethacin group was higher than that in the control group (OR,10.635; 95% CI,1.217–92.94, P = 0.029). There were no significant differences between the two groups in the incidence of other secondary outcomes (P > 0.05 for all). Antenatal indomethacin exposure was found to be associated with PPHN in extremely preterm infants. Therefore, careful consideration and comprehensive assessment were necessary when using indomethacin during pregnancy. Determining the optimal timing for its administration was crucial to minimize the risk of PPHN in this vulnerable population.